Cervical cancer screening and psychosocial barriers perceived by patients. A systematic review - Bukowska-Durawa, Alicja; Luszczynska, Aleksandra (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study: This study aimed at integrating research discussing the role of perceived psychosocial barriers in cervical cancer screening (CCS) uptake. In particular, we analyzed the evidence for the associations between CCS uptake and perceived psychosocial barriers and frequency of psychosocial barriers identified by women. Material and methods : A systematic search of peer-reviewed papers published until 2011 in 8 databases yielded 48 original studies, analyzing data obtained from 155 954 women. The majority of studies (k = 43) applied correlational design, while 5 had experimental design. Results : Experimental research indicated a positive effect of 75% of psychosocial interventions targeting barriers. The interventions resulted in a significant increase of CCS uptake. Overall 100% of correlational studies indicated that perceiving lower levels of barriers significantly predicted higher CCS uptake. 53 psychosocial barriers were listed in at least 2 original correlational studies: 9.5% of barriers were related to CCS facilities/environment, 67.9% dealt with personal characteristics of the patient, and 22.6% addressed social factors. As many as 35.9% of perceived barriers referred to negative emotions related to CCS examination procedures and collecting CCS results, whereas 25.7% of barriers referred to prior contacts with health professionals. Conclusions : Leaflets or discussion on psychosocial barriers between patients and health professionals involved in CCS might increase CCS uptake and thus reduce cervical cancer mortality rates. Communication skills training for health professionals conducting CCS might focus on the most frequently reported barriers, referring to emotions related to CCS examination and collecting CCS results.